Ozone Weekend Effect Analysis in Three European Urban Areas - José Carlos M. Pires (2012)
This paper aims to apply statistical procedures to analyse the ozone weekend effect (OWE) in three European urban areas: Lisbon, Oporto and London. Seasonal variations of surface ozone (O3) and total oxidant species (Ox) concentrations are presented. The studied period was from January 2007 to December 2009. The O3 annual average profile in London was significantly different from the ones achieved for Lisbon and Oporto, due to the high emissions of nitrogen oxides and low temperatures (associated with low solar radiations). The influence of nitrogen oxides in atmospheric chemistry of London was analysed by linear correlations between O3 concentrations and NO2/NO ratio. High values during almost all period showed that O3 concentrations are mainly influenced by NO?NO2?O3 chemical reaction. On the other hand, the linear correlations between O3 and NO2 concentrations only presented positive values in Lisbon and Oporto. This behaviour is associated with photo-dissociation of NO2, producing O3 during the spring and summer periods. Additionally, cluster analysis was applied to group the days of week according the correspondent O3 behaviour. The weekend and some weekdays (immediately after or before) were grouped in the same cluster, showing that OWE occurs in all urban areas selected in this study. These findings suggest that the applied statistical procedures should be used to analyse the OWE and that the causes for the different O3 behaviours during the week may be influenced by meteorological variables.